Peningkatan Prestasi Siswa pada Materi Klasifikasi Makhluk Hidup Menggunakan Video Animasi dengan Model Discovery Learning Kelas VII SMP Al - Maufi Tempurejo - Cici Ilma Arijanah; Diah Sudiarti (FKIP Universitas Islam Jember, 2018)
The learning model is a need for learning in order to achieve success in the education process. The researcher conducted observations in class VII A of Al – Maufi Tempurejo junior high school. The data obtained shows that 47% of students' scores were less equal than 70 (≤70). This study aims to determine student achievement in learning the characteristics of living creatures using animated videos with Discovery Learning models. The type of research used is classroom action research (CAR) with cycle model. Based on the result of the study, the percentage of students’ achievement in the first and second cycles was 88,23%. While the students daily test result on the cycle I and II obtained an average of 89. This proves that using animated videos with discovery learning models can improve student achievement. Animated videos with discovery learning models are used to reduce saturation in the learning process. Keywords: Discovery learning model, learning achievement, animated video